Studies on the Participation of Hageman Factor in Fibrinolysis - McDonagh, R.P, Jr; Ferguson, J.H (Thrombosis and Haemostasis, 1970)
The specific inhibition of the kaolin-mediated Hageman factor activation by the polycations : lysozyme, spermine tetrahydrochloride, and cytochrome c was confirmed. These polycations were without any antiplasmin or antiplasminogen-activator activity when tested in a one-stage lysis system. However, marked inhibition of plasminogen-activator generation in normal plasma by these polycations was noted in the activator-generation test. The proposed role of Hageman factor as that of a lysokinase or indirect activator of plasminogen is supported by these experiments.